Effect of Parental English Proficiency on Psychosocial Functioning in Children with Craniofacial Anomalies. Issue 3 (March 2020) - De Leon, Fransia S.; Pfaff, Miles J.; Volpicelli, Elizabeth J.; Potemra, Hi'ilani M. K.; Lin, Johnny; Ayeroff, Julia R.; Bradley, James P.; Wilson, Libby F.; Lee, Justine C.
Abstract : Background: Psychosocial distress in children with craniofacial anomalies is multifactorial. A known cause of childhood psychosocial distress is parental limited English proficiency; however, its role as a psychosocial stressor in the craniofacial anomaly population remains unknown. The current study aimed to understand the potential influence of parental English proficiency in children with craniofacial anomalies. Methods: Two hundred ninety-six children were prospectively evaluated at the University of California, Los Angels and the Orthopaedic Institute for Children using the Pediatric Patient-Reported Outcomes Measurement Information System to assess anger, anxiety, depression, and peer relationships. Children were grouped by parental English proficiency based on the requirement or lack thereof for interpreting services during clinic appointments. Independent t tests, analyses of variance, and linear regressions were performed to compare groups and identify predictors for psychosocial functioning. Results: Although comparison children did not exhibit any differences in psychosocial scores with respect to parental English proficiency, craniofacial anomaly children with parents who have limited English proficiency demonstrated higher anger, anxiety, depression, and lower peer relationships compared with those with parents who are English proficient. Linear regression analyses demonstrated that limited English proficiency in parents was a significant predictor for anger ( p = 0.005), anxiety ( p = 0.002), depression ( p < 0.001), and poor peer relationships ( p < 0.001) in children with craniofacial anomalies. Conclusions: Parental English proficiency is associated with increased psychosocial distress in children with craniofacial anomalies. Future efforts toward identification of and assistance for parents with limited English proficiency to address barriers to care may improve psychosocial function in children with craniofacial anomalies. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.